2017
DOI: 10.4196/kjpp.2017.21.6.657
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of combination treatment of gabapentin and electro-acupuncture on paclitaxel-induced neuropathic pain

Abstract: Paclitaxel, a chemotherapeutic drug, induces severe peripheral neuropathy. Gabapentin (GBT) is a first line agent used to treat neuropathic pain, and its effect is mediated by spinal noradrenergic and muscarinic cholinergic receptors. Electro-acupuncture (EA) is used for treating various types of pain via its action through spinal opioidergic and noradrenergic receptors. Here, we investigated whether combined treatment of these two agents could exert a synergistic effect on paclitaxel-induced cold and mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…Gabapentin binds with the α2δ subunit of the calcium channel [30]. Findings from this study revealed that gabapentin reverses both thermal and mechanical hypersensitivities, a finding which is in consonant with those of Kim et al [31] in an animal model of neuropathic pain. The antinociceptive effects of gabapentin in a CCI model of neuropathic pain were similar to those of bromelain, although pretreatment with bromelain has a stronger effect on thermal hyperalgesic symptoms and the SFI.…”
supporting
confidence: 89%
“…Gabapentin binds with the α2δ subunit of the calcium channel [30]. Findings from this study revealed that gabapentin reverses both thermal and mechanical hypersensitivities, a finding which is in consonant with those of Kim et al [31] in an animal model of neuropathic pain. The antinociceptive effects of gabapentin in a CCI model of neuropathic pain were similar to those of bromelain, although pretreatment with bromelain has a stronger effect on thermal hyperalgesic symptoms and the SFI.…”
supporting
confidence: 89%
“…5,6 In addition, combined treatment with EA and gabapentin (an analgesic drug) showed robust and enduring analgesic actions against PTX-induced neuropathy. 7 Furthermore, a phase IIA trial showed that acupuncture attenuated the severity of peripheral neuropathy induced by PTX chemotherapy in breast cancer patients. 8 According to previous basic studies, the anti-nociceptive effect of EA in relieving PTX-induced neuropathic pain was mediated via spinal opioid receptors and the adrenergic pathway, which is similar to the mechanism underlying EA's analgesic actions in other pain models.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, BVA significantly attenuated cold and mechanical allodynia induced by oxaliplatin. Moreover, BVA induced an additive effect when simultaneously injected with morphine by increasing the action time in mice injected with a chemotherapeutic agent [8]. Furthermore, three weeks of treatment with BVA in patients with chemotherapy-induced neuropathic pain also resulted in positive effects [21], implying the efficacy of BVA against oxaliplatin-induced neuropathic pain.…”
Section: Introductionmentioning
confidence: 96%
“…For the past several years, our group has focused on understanding the underlying mechanism of oxaliplatin-induced neuropathic pain and on finding an effective treatment method. The effects of well-known analgesic drugs such as morphine [7], gabapentin [8], and duloxetine [9] have been assessed along with herbal medicines [10][11][12], acupuncture [8,13], and bee venom acupuncture (BVA) [7,[14][15][16]. Bee venom (BV) is composed of peptides, enzymes, amines, and non-peptide components that have a variety of pharmaceutical properties [17].…”
Section: Introductionmentioning
confidence: 99%